2008
DOI: 10.1590/s1413-86702008000300013
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between serum tumor necrosis factor alpha levels and clinical severity of tuberculosis

Abstract: This study verified the correlation between the serum levels of TNF alpha and different clinical forms of tuberculosis. We described a group of 24 patients presenting several clinical forms of tuberculosis and a control group of 13 healthy individuals. The levels of TNF alpha were measured by bioassay method. The levels of TNF-alpha had significant differences between the tuberculosis and control groups. The patients with abnormal chest X-Ray findings had higher TNF alpha levels (15328.48 ± 4602.19 pg/mL) when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 34 publications
4
8
2
Order By: Relevance
“…The reason why animals vaccinated with BCG combined with drug therapy gained significantly less weight compared to the RHZ alone group is unclear. One possible explanation is the release of proinflammatory cytokines like TNF-α which have been shown to contribute to the weight loss seen in human patients with active M. tuberculosis infections [46]. Among the few differences that was seen in the change in body temperature was an increase in the animals that received BCG and RHZ.…”
Section: Discussionmentioning
confidence: 99%
“…The reason why animals vaccinated with BCG combined with drug therapy gained significantly less weight compared to the RHZ alone group is unclear. One possible explanation is the release of proinflammatory cytokines like TNF-α which have been shown to contribute to the weight loss seen in human patients with active M. tuberculosis infections [46]. Among the few differences that was seen in the change in body temperature was an increase in the animals that received BCG and RHZ.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, excessive levels of TNF‐α may cause tissue damage in vivo , 34 including hyperinflammation, caseous necrosis and cachexia 37 . Moreover, it has been reported that a correlation exists between TNF‐α levels and clinical severity of human TB 38 . Furthermore, the function of TNF‐α in humans is of clinical interest due to the association of anti‐inflammatory TNF‐blocking drugs with reactivation of latent TB 39 , 40 …”
Section: Discussionmentioning
confidence: 99%
“…Another previous study also showed that there was an association of TNF-α levels, blood glucose levels and HbA1c in type 2 diabetic patients [26]. Study by de Andrade Junior et al, showed that the increasing levels of TNF-α related to the severity and complications in tuberculosis infection [27]. In tuberculosis infection, disruption of immune system of the body carried out by Mtb.…”
Section: Discussionmentioning
confidence: 91%